Fermionic Condensate on Finite Radius Cones - Hovhannisyan, A. A.
The fermionic condensate is investigated for a field localized on a finite radius 2- dimensional cone in the presence of a magnetic flux threading the cone apex. On the edge of the cone a boundary condition is imposed that differs from the MIT bag boundary condition, most frequently used for the confinement of fermions. The fermionic condensate is decomposed into the boundary-free and edge-induced contributions. Both these parts are periodic functions of the magnetic flux with the period equal to the flux quantum.
Keywords: Physics